Method for detecting breakage of non-metal cellosilk in concrete structure

By adding fluorescent nanoparticles, conductive graphene microsheets and liquid sulfur hexafluoride microcapsules into the adhesive, and combining drone inspections and electrical detection methods, efficient and accurate detection of broken non-metallic fiber filaments inside concrete structures is achieved, solving the detection problem.

CN120778746APending Publication Date: 2025-10-14六合郑大科学技术转化中心 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510959424.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

Existing non-destructive testing technologies have difficulty in effectively detecting the breakage of non-metallic fiber filaments inside concrete structures, especially due to their tiny size, flexibility and weak damage signals.

Method used

Microcapsules containing fluorescent nanoparticles, conductive graphene microsheets and liquid sulfur hexafluoride are added to the adhesive, and the location of the broken wire is determined through drone inspection, electrical signal detection and gas detection methods.

Benefits of technology

The accuracy and feasibility of detecting broken non-metallic fiber wires inside concrete structures are improved, solving the engineering problem of difficulty in detecting broken non-metallic fiber wires.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120778746A_ABST
    Figure CN120778746A_ABST
Patent Text Reader

Abstract

The invention discloses a method for detecting breakage of non-metal cellosilk in a concrete structure, belongs to the field of nondestructive testing, and comprises a method for mixing microcapsules in a combined colloid and a method for detecting leakage of microcapsule wrappage. Wherein the microcapsule doping in the combined colloid refers to that three microcapsules which respectively wrap fluorescent nanoparticles, conductive graphene nanoplatelets and liquid sulfur hexafluoride are doped into an adhesive during fiber arrangement, and when the fibers are broken, microcapsule wrappings leak out, so that the fluorescent nanoparticles, the conductive graphene nanoplatelets and the liquid sulfur hexafluoride are uniformly distributed. And the broken wire position is determined through unmanned aerial vehicle inspection, electric signal detection and a gas detection method. The method for detecting the broken fibers in the concrete structure is high in measurement accuracy and good in feasibility, and the engineering problem that broken non-metal fibers in concrete are difficult to detect is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of non-destructive testing, in particular to a structure internal damage and fracture detection technology, and more particularly to a method for detecting broken non-metallic fiber wires inside a concrete structure. Background Art

[0002] With the continuous development of modern engineering structures, fiber-reinforced composites (FRPs) have become key materials in fields such as construction and aerospace due to their excellent mechanical properties and durability. However, fiber filaments can suffer damage such as breakage and wear during use, which can seriously affect the safety and service life of the structure. Therefore, higher requirements are placed on non-destructive testing (NDT) technologies for fiber filaments. Among existing NDT technologies, steel wire inspection is relatively mature. As a traditional engineering material, steel wire inspection methods primarily include electromagnetic testing and visual inspection. For example, magnetostrictive testing enables rapid, non-contact inspection over a wide range, effectively detecting covered or deeply buried steel components with high efficiency. Furthermore, the relatively simple structure of steel wire ropes results in more distinct damage signal signatures, facilitating defect identification through signal processing techniques. In contrast, the inspection of non-metallic fiber filaments is significantly more challenging. Non-metallic fiber filaments typically have micron-scale diameters, extremely small cross-sections, and high flexibility, making them extremely susceptible to damage during inspection. Furthermore, the damage signals from non-metallic fiber filaments are typically weak and easily interfered with by environmental noise, further complicating detection. In summary, the detection of non-metallic fiber filaments within structures presents more technical challenges than that of steel wires. The tiny size, flexibility, and weak damage signals of non-metallic fiber filaments make them difficult to directly apply to fiber filament inspection using existing detection technologies. Therefore, developing an efficient and accurate non-destructive testing method for fiber filaments is of great practical significance for ensuring the safety and reliability of fiber-reinforced composite structures.

[0003] To address these issues, the present invention proposes a method for detecting broken non-metallic fibers within concrete structures. During fiber placement, three types of microcapsules containing fluorescent nanoparticles, conductive graphene flakes, and liquid sulfur hexafluoride are incorporated into the adhesive. When a fiber breaks, the microcapsule contents leak out, allowing the location of the broken fiber to be determined through drone inspections, electrical signal detection, and gas detection. This method offers high accuracy and robust feasibility, resolving the engineering challenge of detecting broken non-metallic fibers within concrete.

[0004] After checking, no published patents involve technology for detecting broken non-metallic fiber filaments inside concrete. Summary of the Invention

[0005] Based on the above-mentioned problem that the small size, flexibility and weak damage signal of non-metallic fiber wires make it difficult to detect their broken wires, a method for detecting broken non-metallic fiber wires inside concrete structures is provided to provide technical support for the problem of detecting broken non-metallic fiber wires inside concrete.

[0006] The present invention provides a method for detecting broken non-metallic fiber wires inside a concrete structure, characterized in that the method comprises the following steps:

[0007] S1: Preparation of fluorescent nanoparticle microcapsules, conductive graphene microsheet microcapsules and liquid sulfur hexafluoride microcapsules;

[0008] S2: adding microcapsules to an adhesive and bonding the fiber filaments with the adhesive;

[0009] S3: Arrange the fiber filaments inside the concrete structure and cover it with a copper mesh electrode array;

[0010] S4: After the wire is broken, the location of the broken wire is determined by drone inspection, telecommunication signal detection and gas detection.

[0011] Furthermore, the step S1 includes a method for preparing fluorescent nanoparticle microcapsules.

[0012] Preferably, zinc sulfide-doped copper nanoparticles can be used to prepare fluorescent nanoparticle microcapsules, with zinc nitrate, sodium sulfide, and copper sulfate as precursors, sodium lauryl sulfate as a surfactant, and a mixed solution of deionized water and ethanol as a solvent.

[0013] Preferably, a hydrothermal method can be used to prepare fluorescent nanoparticles: zinc nitrate and copper sulfate are dissolved in deionized water and stirred until completely dissolved. Sodium sulfide is dissolved in deionized water and slowly added dropwise to the mixture. Sodium lauryl sulfate is added as a dispersant and stirring is continued. The mixture is transferred to a polytetrafluoroethylene-lined autoclave, heated at 180°C for 12 hours, and then cooled naturally to room temperature. Post-processing is then performed using a centrifuge to obtain the fluorescent nanoparticles.

[0014] Preferably, the fluorescent nanoparticles are mixed with a low-viscosity epoxy repair agent using microfluidic technology, ultrasonically dispersed for 30 minutes, and the polyurethane prepolymer is dissolved in dichloromethane and cross-linked at 50°C under nitrogen protection for 4 hours to complete the preparation.

[0015] Furthermore, according to the method for detecting broken non-metallic fiber filaments inside a concrete structure according to claim 1, it is characterized in that the step S1 includes a method for preparing conductive graphene microsheet microcapsules.

[0016] Preferably, high-quality graphene microsheets are used as the conductive material, methylated hexahydroxymethyl melamine resin prepolymer is used as the wall material, polystyrene maleic anhydride copolymer is used as the dispersant, isophorone diisocyanate is used as the coating repair agent, and deionized water is used as the solvent.

[0017] Preferably, the dispersant is added to deionized water for mixing and swelling, and the pH value of the solution is adjusted to 10-11, and then the solution is dispersed for the first time; the coating repair agent is added to the solution after the first dispersion, and a second dispersion and emulsification are performed.

[0018] Preferably, methylated hexamethylolmelamine resin prepolymer and polyvinyl alcohol are added to the emulsified solution, stirred, and then heated to continue the reaction to obtain a mixed solution I.

[0019] Preferably, a mixture of methylated hexahydroxymethyl melamine resin prepolymer and graphene microsheets is added to the mixed solution I, and then the mixture is slowly added so that the methylated hexahydroxymethyl melamine resin prepolymer and graphene are uniformly adsorbed on the core droplets through charge action; the temperature is raised to 70°C to 80°C, the pH value of the mixed solution II is adjusted to 3 to 5, the reaction is continued to obtain a mixed solution III.

[0020] Preferably, the temperature of the mixed solution III is lowered to room temperature, and after filtration and drying, microcapsules based on graphene microsheets are obtained.

[0021] Furthermore, according to the method for detecting broken non-metallic fiber filaments inside a concrete structure according to claim 1, it is characterized in that the step S1 includes a method for preparing liquid sulfur hexafluoride microcapsules.

[0022] Preferably, liquid CO2 is introduced into an autoclave, heated and pressurized to a supercritical state; then, liquid sulfur hexafluoride is injected and mixed with the supercritical CO2 to form a homogeneous solution; the ethyl acetate solution of PVDF / PLA is atomized and sprayed into the autoclave, and the supercritical CO2 rapidly extracts the solvent, causing the polymer to deposit into a shell on the surface of the SF4 droplets; then, the pressure is slowly reduced to normal pressure, the CO2 gasifies and escapes, and the sulfur hexafluoride remains in a liquid state due to the sealing of the shell layer.

[0023] Furthermore, the step S2 includes a microcapsule incorporation method.

[0024] Preferably, the fluorescent nanoparticle microcapsules, the conductive graphene microsheet microcapsules and the liquid sulfur hexafluoride microcapsules are added to the liquid adhesive in batches, with the mass fraction of each batch being 1%, and the mixture is uniformly stirred.

[0025] Furthermore, the step S2 also includes a fiber bonding method.

[0026] Preferably, for a prestressed structure, the fiber filaments are first fixed to the structure, and a set prestress is applied to the fiber filaments, and the prestress on the fiber filaments is allowed to stabilize, and then the fiber filaments are covered with an adhesive and the adhesive is allowed to completely solidify.

[0027] Preferably, for non-prestressed structures, multiple fiber strands are first bonded together with an adhesive to prefabricate the reinforcement and other patterns required for the structure. After the adhesive is completely cured, the surface leakage signal is detected and the finished products with intact microcapsules are arranged inside the concrete structure.

[0028] Furthermore, the step S3 includes a method for installing a copper mesh electrode array.

[0029] Preferably, nylon ties are used to fix the copper mesh and FRP bars, and graphite-modified cement mortar is filled between the copper mesh and the fiber filaments to ensure the current conduction path. The terminal blocks are encapsulated with epoxy resin, the signal lines use twisted pair cables and aluminum foil shielding layers, and a grounding wire is set. The initial resistance value is measured 7 days after pouring (after the concrete hardening is completed) as the baseline data.

[0030] Furthermore, step S4 includes a method for determining the location of the broken wire by combining drone inspection, electrical signal detection, and gas detection.

[0031] Preferably, a UV camera is mounted on a drone, and by compiling an inspection route, the fluorescent area on the surface of the structure is photographed, and then combined with an image recognition algorithm, the location where the fiber breakage is suspected to have occurred is circled.

[0032] Preferably, at the location where the fiber breakage is suspected to have occurred, which is circled by the drone, a multi-channel resistance meter is used to connect the electrode nodes to detect the resistance between adjacent electrodes. If the resistance in a certain area drops by >50%, a broken wire alarm is triggered, and the coordinates are determined by the intersection area of ​​the resistance mutation electrodes.

[0033] Preferably, a sniffer is used to scan the leakage point of sulfur hexafluoride along the surface of the structure to further confirm the degree and location of the broken wire.

[0034] Furthermore, the step S4 also includes inverting the sulfur hexafluoride leakage source using a Gaussian plume model, and further determining the location and intensity of the leakage source.

[0035] Compared with the prior art, the advantages and positive effects of the present invention are:

[0036] This invention provides a method for detecting broken non-metallic fibers within concrete structures. Compared to existing technologies, this method employs a binder containing three types of microcapsules—one containing fluorescent nanoparticles, one containing conductive graphene microplatelets, and one containing liquid sulfur hexafluoride—incorporated into the fibers. When a fiber breaks, the microcapsule contents leak out, allowing the location of the broken fiber to be determined through drone inspections, electrical signal detection, and gas detection. This method offers high accuracy and feasibility, resolving the engineering challenge of detecting broken non-metallic fibers within concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0038] Figure 1 A schematic diagram of adding fluorescent nanoparticle microcapsules, conductive graphene microsheet microcapsules and liquid sulfur hexafluoride microcapsules provided in Example 4;

[0039] Figure 2 A schematic diagram of an improved method for detecting wire breakage in a corrugated steel fiber reinforced tube at a trough provided in Example 5;

[0040] In the above figures, 1. Fluorescent nanoparticle microcapsules; 2. Conductive graphene microsheet microcapsules; 3. Fiber filaments; 4. Liquid sulfur hexafluoride microcapsules; 5. Copper mesh electrode array; 6. Adhesive; 71. Fiber-doped mortar; 72. Circumferential steel bars; 73. Spiral corrugated steel cylinder; 74. Unsaturated resin; 75. Longitudinal steel bars; 76. PE protective cover; 77. Copper mesh; 78. Basalt fiber filaments. DETAILED DESCRIPTION

[0041] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other in the absence of conflict.

[0042] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0043] Example 1: This example aims to implement a method for preparing fluorescent nanoparticle microcapsules. When preparing fluorescent nanoparticle microcapsules, the following steps need to be followed to ensure the success rate of the preparation:

[0044] 1. The core material is zinc sulfide doped copper nanoparticles (ZnS:Cu), which has high stability and resistance to photobleaching. 2+ The doping concentration is 0.5% by mole (ZnS:Cu=99.5:0.5).

[0045] 2. The precursors selected are zinc nitrate (Zn(NO3)2), sodium sulfide (Na2S), and copper sulfate (CuSO4); the surfactant selected is sodium dodecyl sulfate (SDS) or polyvinylpyrrolidone (PVP); and the solvent selected is a mixed solution of deionized water and ethanol (volume ratio 3:1).

[0046] 3. Dissolve 0.1 mol Zn(NO3)2 and 0.0005 mol CuSO4 in 200 ml of deionized water and stir until completely dissolved; dissolve 0.15 mol Na2S in 100 ml of deionized water and slowly add it dropwise to the above mixture. Add 0.5 g SDS as a dispersant and continue stirring for 1 hour.

[0047] 4. Transfer the mixture to a polytetrafluoroethylene-lined autoclave with a filling degree of 70%. Keep the mixture at 180°C for 12 hours and then cool it naturally to room temperature.

[0048] 5. Centrifuge at 8000 rpm for 10 minutes, collect the precipitate; wash with deionized water and ethanol three times each, and dry in vacuo at 60°C for 6 hours to obtain light green ZnS:Cu nanopowder.

[0049] 6. The particle size was controlled by adjusting the hydrothermal temperature and time, with a target size of 50 ± 5 nm (optimized conditions were 160 ° C / 14 hours); 3-aminopropyltriethoxysilane (APTES) was used for surface modification to enhance compatibility with the resin matrix.

[0050] 7. ZnS:Cu nanoparticles (10 wt%) were mixed with a low-viscosity epoxy repair agent and ultrasonically dispersed for 30 minutes; polyurethane (PU) prepolymer was dissolved in dichloromethane (concentration 20 wt%); curing conditions: cross-linking at 50°C under nitrogen protection for 4 hours.

[0051] Example 2: This example aims to implement a method for preparing conductive graphene microcapsules. When preparing conductive graphene microcapsules, the following steps need to be followed to ensure the success rate of the preparation:

[0052] 1. Add the dispersant (SMA) to deionized water and mix and swell; adjust the pH value of the solution to 10-11; disperse the solution for the first time for 20-30 minutes; add the coating repair agent (IPDI) to the solution after the first dispersion and perform a second dispersion and emulsification for 10-15 minutes.

[0053] 2. Add methylated hexamethylolmelamine resin prepolymer and polyvinyl alcohol to the emulsified solution with a stirring speed of 500 r / min for 10 minutes, then raise the temperature to 50°C to 60°C and continue the reaction for 1 hour to obtain a mixed solution I.

[0054] 3. Add a mixture of methylated hexahydroxymethylmelamine resin prepolymer and graphene microplatelets to mixed solution I at a rate of 0.8 ml / min to 1.0 ml / min, so that the methylated hexahydroxymethylmelamine resin prepolymer and graphene are uniformly adsorbed on the core droplets through charge interaction. Continue to heat the mixture to 70°C to 80°C, adjust the pH value of mixed solution II to 3 to 5, and continue the reaction to obtain mixed solution III.

[0055] 4. The temperature of the mixed solution III is lowered to room temperature; filtered and dried to obtain microcapsules based on graphene microsheets.

[0056] Example 3: This example aims to implement a method for preparing liquid sulfur hexafluoride microcapsules. When preparing liquid sulfur hexafluoride microcapsules, the following steps need to be followed to ensure the success rate of the preparation:

[0057] 1. Liquid CO2 is introduced into the autoclave, heated to 35°C and pressurized to 10 MPa to reach a supercritical state (density 0.6 g / cm 3 ); inject liquid SF6 (pre-cooled to -20°C) and mix it with supercritical CO2 to form a homogeneous solution (SF6 accounts for 15wt%).

[0058] 2. A PVDF / PLA ethyl acetate solution (10 wt%) was atomized and sprayed into an autoclave with droplets of 50-100 μm in diameter. Supercritical CO2 rapidly extracted the solvent, causing the polymer to form a shell on the surface of the SF6 droplets. The pressure was slowly reduced to ambient pressure, and the CO2 vaporized and escaped. The SF6 remained liquid due to the sealed shell, and the internal pressure self-balanced to 3 atm.

[0059] Example 4: This example aims to implement an improved example of detecting broken wires in the troughs of corrugated steel fiber reinforced tubes. When performing broken wire detection, the following steps need to be followed to ensure successful detection:

[0060] 1. When preparing the fiber reinforcement layer, fluorescent nanoparticle microcapsules (1), conductive graphene microsheet microcapsules (2) and liquid sulfur hexafluoride microcapsules (4) are added to the unsaturated resin (74) in batches at a ratio of 1% by mass and uniformly stirred.

[0061] 2. Wrapping basalt fiber filaments (78) in the troughs and covering each layer of fiber filaments with an unsaturated resin containing microcapsules.

[0062] 3. After welding the longitudinal steel bars (75) and the circumferential steel bars (72) on the corrugated steel cylinder (73), a copper mesh (77) is installed on the surface of the fiber reinforced layer.

[0063] 4. Use nylon tie to fix the copper mesh (77) and the fiber reinforcement layer, and fill graphite modified cement mortar between the copper mesh (77) and the basalt fiber (78) to ensure the current conduction path.

[0064] 5. Use epoxy resin to encapsulate the terminal blocks, use twisted-pair cables with aluminum foil shielding for the signal lines, and provide a grounding wire. Measure the initial resistance value seven days after pouring as the baseline data.

[0065] 6. Mount a UV camera on a drone and, by compiling an inspection route, capture fluorescent areas on the surface of the structure. Combined with an image recognition algorithm, it can pinpoint locations where fiber breaks are suspected.

[0066] 7. At the suspected broken wire location identified by the drone, a multi-channel resistance meter is used to connect the electrode nodes and measure the resistance between adjacent electrodes. If the resistance in a certain area drops by more than 50%, a broken wire alarm is triggered. The broken wire coordinates are determined by the intersection of the electrodes with the sudden change in resistance.

[0067] 8. Use a sniffer to scan the leakage point of sulfur hexafluoride along the surface of the structure to further confirm the degree and location of the broken wire.

[0068] 9. The SF6 leakage source is inverted through the Gaussian plume model to further determine the location and intensity of the leakage source, thereby accurately determining the location of the broken wire.

Claims

1. A method for detecting broken non-metallic fiber wires inside a concrete structure, characterized in that: The method for detecting broken non-metallic fiber wires inside a concrete structure comprises the following steps: S1: Preparation of fluorescent nanoparticle microcapsules (1), conductive graphene microsheet microcapsules (2) and liquid sulfur hexafluoride microcapsules (4); S2: adding microcapsules to a binder (6), and bonding the fiber filaments (3) with the binder (6); S3: Arrange the fiber filaments inside the concrete structure and cover the copper mesh electrode array (5); S4: After the wire is broken, the location of the broken wire is determined by drone inspection, telecommunication signal detection and gas detection.

2. A method for detecting broken non-metallic fiber wires inside a concrete structure according to claim 1, characterized in that: The step S2 includes a microcapsule incorporation method: Fluorescent nanoparticle microcapsules (1), conductive graphene microsheet microcapsules (2) and liquid sulfur hexafluoride microcapsules (4) are added to a liquid adhesive (6) in batches, with the mass fraction of each batch being 1%, and stirred evenly.

3. The method for detecting broken non-metallic fiber wires inside a concrete structure according to claim 1, characterized in that: The step S2 further comprises a fiber bonding method: For a prestressed structure, the fiber filament (3) is first fixed on the structure, and a set prestress is applied to the fiber filament (3), and the prestress on the fiber filament (3) is allowed to stabilize. Then, the fiber filament (3) is covered with an adhesive (6), and the adhesive (6) is allowed to completely solidify. For non-prestressed structures, a plurality of fiber strands (3) are first bonded together with an adhesive (6) to prefabricate the required reinforcement material and other patterns of the structure. After the adhesive (6) is completely cured, the surface leakage signal is detected and the finished product with intact microcapsules is arranged inside the concrete structure.

4. The method for detecting broken non-metallic fiber wires inside a concrete structure according to claim 1, characterized in that: The step S3 includes a method for installing a copper mesh electrode array: Nylon cable ties were used to secure the copper mesh to the FRP bars, and graphite-modified cement mortar was filled between the copper mesh and the fiber filaments to ensure a current conduction path. Epoxy resin was used to encapsulate the wiring terminals, and twisted-pair cables and aluminum foil shielding were used for the signal lines. A grounding wire was also provided. The initial resistance value was measured 7 days after pouring (after the concrete had hardened) as the baseline data.

5. The method for detecting broken non-metallic fiber wires inside a concrete structure according to claim 1, characterized in that: The step S4 includes a method for determining the location of the broken wire by combining drone inspection, electrical signal detection, and gas detection: A UV camera is mounted on a drone, which compiles an inspection route to capture fluorescent areas on the surface of the structure. This is then combined with an image recognition algorithm to pinpoint locations where fiber breaks are suspected. At the location where the UAV has circled the suspected fiber breakage, a multi-channel resistance meter is used to connect the electrode nodes to measure the resistance between adjacent electrodes. If the resistance in a certain area drops by more than 50%, a broken wire alarm is triggered, and the coordinates are determined by the intersection area of ​​the electrodes where the resistance mutation occurs. Use a sniffer to scan the sulfur hexafluoride leakage point along the surface of the structure to further confirm the degree and location of the broken wire.

6. The method for detecting broken non-metallic fiber wires inside a concrete structure according to claim 1, characterized in that: The step S4 further includes inverting the leakage source of sulfur hexafluoride using a Gaussian plume model, and further determining the location and intensity of the leakage source.